1115. Use of a Fluoroquinolone (FQ) vs. a Non-Fluoroquinolone (Non-FQ)-Based Antibiotic Regimen in the Treatment of Acute, Uncomplicated Diverticulitis. (26th November 2018) - Mourani, Jessyca; Postelnick, Michael; Martin, David
Abstract: Background: The management of acute, uncomplicated diverticulitis (DVT) remains based on expert consensus rather than on evidence from randomized clinical trials. The most common antibiotic (AB) regimen used in this patient population is metronidazole plus a fluoroquinolone (FQ). Non-FQ options, including B-lactam and non B-lactam regimens are available. Since there is a lack of clinical data comparing outcomes between these regimens, it remains uncertain whether patients presenting with acute, uncomplicated DVT require a FQ-based regimen. Increasing rates of FQ resistance and awareness of collateral damage have raised concern about whether this class should remain a first-line option. Methods: This retrospective cohort study was conducted utilizing electronic health records to identify patients 18 years of age or older with acute, uncomplicated DVT, defined by ICD 10 codes. Patients included had CT confirmed DVT and were started on a guideline recommended AB regimen. Data points collected included length of stay, 30-day readmission due to DVT, time to conversion from IV to PO AB, progression to surgery, and discharge AB regimen. The primary objective is to evaluate differences in length of stay and 30 day re-admission rates. The secondary objectives are to evaluate time from intravenous (IV) to oral (PO) AB, progression to surgery, and discharge AB between the two groups. Results: 136 patients were evaluated, 71 FQ and 65 non-FQ. Length of stay was 4 days (1–18) in the FQ group vs. 5 days (1–19) in the non-FQ group ( P = 0.236). 11% of patients in the FQ group vs. 9% of patients in the non-FQ group had a DVT related 30 day readmission ( P = 0.451). 22% of patients in the FQ group vs. 23% of patients in the non-FQ group progressed to GI surgery during the admission. Time from IV to PO conversion of AB was 34.2 hours (0–63) in the FQ group vs. 48.4 hours (0–81) hours in the non-FQ group. Lastly, 63 of the 71 patients who were started on a FQ were discharged on an oral FQ vs. Forty patients of the 65 patients started on a non-FQ were discharged on an oral FQ Conclusion: In the treatment of acute, uncomplicated DVT outcomes including length of stay, 30-day readmission, time from IV to PO AB, and progression to surgery were comparable in patients receiving treatment with a FQ based AB regimen vs. a non-FQ based regimen. Disclosures: D. Martin, GlaxoSmithKline: Independent Contractor, Salary Syneos Health: Employee, Salary.